Case Study of Social Sustainability Practices in U.S. Small Hub Airports. Issue 10 (October 2021) - Marete, Caroline K.; Johnson, Mary E.
Airports have economic, environmental, and social impacts on communities. Many of these impacts are influenced by airport management decisions. Airport sustainability may be thought of as having four primary areas: environmental, economic, operational, and social. The objective of this study is to understand better the adoption of social sustainability practices in small hub airport planning in the United States. The small hub airports in this study participated in the Federal Aviation Administration Airport Improvement Program for sustainability planning and have published their sustainability plans as either standalone sustainability management plans or integrated sustainable master plans. Plans from the six airports were gathered and examined as part of an exploratory case study analysis. The findings show that small hub airports do not use the same framework or select the same practices for social sustainability. Social sustainability practices for these six small hub airports focus on four stakeholder categories: passengers and travelers, employees, communities and local businesses, and concessionaires and tenants.